KAJIAN SIFAT FISIKA DAN KIMIA TANAH INCEPTISOL PADA LAHAN KARET TELAH MENGHASILKAN DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTPN III SARANG GITING (Study of Physical and Chemical Inceptisol Soil Characteristic on Produced Rubber Plantation with - Sri Apulina; Sumono Sumono; Ainun Rohanah (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT Physical and chemical soil characteritics are important factors for the growth of rubber plant. This research was aimed to study physical and chemical soil characteritics of the rubber plant with vegetations of  harupat spikes, grass, taro and no vegetation in Pagar Merbau PTP Nusantara II. The observed parameters were soil texture, porosity, water content of field capasity, soil permeability, total Nitrogen, available Phospate, and land Potassium exchange. The results showed that the soil type was ultisol, with sandy loam texture and pH of 4,62-4,97 (acid). The vegetation soil had porosity of 51,75-52,73 % at a depth of 5 cm and 51,35-53,30 % at a depth of 25 cm. The water content of field capacity was ranged from 40,9-44,3 % at a depth of 5 cm and 32,9-35,3 % at a depth of 25 cm. Permeability was ranged from 3,57-5,89 cm/h. Total N was 0,06-0,09 %. P available was ranged from 9,77-15,37 ppm. K exchange of land was ranged from 0,66-0,85 me/100g. The soil with no vegetation had porosity of 51,34  % at a depth of 5 cm and 50,95  % at a depth of 25 cm. The water content of field capacity was 35,1 % at a depth of 5 cm and 29 % at a depth of 25 cm. Permeability was 2,62 cm/h. Total N was 0,06 %. P available was 14,99 ppm. K exchange of land was 0,83 me/100g. Keywords: Soil physical and chemical, vegetation, rubber plantation, inceptisol ABSTRAK Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan karet. Penelitian ini bertujuan untuk mengkaji sifat fisika dan kimia tanah inceptisol pada lahan karet dengan vegetasi paku harupat, rumput, keladi dan tanpa vegetasi di Kebun PTP. Nusantara III Sarang Giting. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabilitas tanah, N-total, P tersedia dan K tukar tanah. Hasil penelitian menunjukkan jenis tanah di daerah penelitian adalah inceptisol bertekstur lempung berliat, lempung berpasir, dan pasir berlempung dengan pH 4,62-4,97 (masam). Tanah dengan vegetasi mempunyai porositas berkisar 51,75-52,73 % pada kedalaman 5 cm dan 51,35-53,30 % pada kedalaman 25 cm, kadar air kapasitas lapang 40,9-44,3 % pada kedalaman 5 cm dan 32,9-35,3 % pada kedalaman 25 cm, permebilitas berkisar 3,57-5,89 cm/jam, N-total 0,06-0,09 %, P tersedia 9,77-15,37 ppm, K tukar tanah 0,66-0,85 me/100g. Tanah tanpa vegetasi mempunyai porositas berkisar 51,34 % pada kedalaman 5 cm dan 50,95 % pada kedalaman 25 cm, kadar air kapasitas lapang 35,1 % pada kedalaman 5 cm dan 29 % pada kedalaman 25 cm, permebialitas berkisar 2,62 cm/jam, N-total 0,06 %, P tersedia 14,99 ppm, K tukar tanah 0,83 me/100g. Kata Kunci: Fisika dan kimia tanah, vegetasi, kebun karet, inceptisol